Answer:
D
Step-by-step explanation:
step 2 : x + 3 = 0 and x - 5 = 0 ← correct
step 3
x = 3 and x = - 5 ← error made here with signs, correct statement should be
x + 3 = 0 ⇒ x = - 3
x - 5 = 0 ⇒ x = 5
Answer:
i think theres a typo somewhere
Step-by-step explanation:
Answer:
60%
Step-by-step explanation:
36/60 x 100= 60%
-4x-2y = 16
2y = -4x-16
Get one variable alone on both equations
-4x - 16 = 2y
-4x - 16 = 2y
You'll realize that they're the same equation.
Use substitution
-4x-16 = -4x-16
0 = 0
x = all solutions
Use x = all solutions in an earlier equation to find y
-4x - 16 = 2y
SInce x can be all solutions y is also all solutions
y = all solutions